Bridging the Competency Gap: Aligning Automotive Vocational Education with Industrial Standards in Industrial Work Placement Programs - Ngatou Rohman; Rasyid Sidik; Suwantri Suwantri (MASI Mandiri Edukasi, 2026)
Background: Industrial Work Placement (PKL) is a mandatory course for Vocational High School (SMK) students involving practical activities in relevant industries. A significant gap persists between the competencies students have mastered and the professional standards required by the automotive industry. Objective: This study aims to identify the competency standards required for automotive engineering (TKRO) students to perform effectively during industrial work placement, in accordance with automotive industry requirements. Methodology: This research employed a qualitative case study design. Data were collected through in-depth semi-structured interviews with nine purposively selected automotive workshop managers in Surakarta, Indonesia. Data analysis followed the interactive model of Miles, Huberman, and Saldana (2014). Findings: To successfully execute tasks in the automotive industry, internship students must possess a triad of competencies: (1) general competencies (soft skills) including occupational health and safety, industrial culture, and work environment maintenance; (2) specific/technical competencies (hard skills) covering inspection and maintenance of engines, power transmission, electrical, and body electrical systems; and (3) automotive-specific supporting competencies related to digital literacy and modern automotive technology. Practical Implications: The findings provide a concrete reference for vocational curriculum design and student preparation before industrial placement, particularly in the context of Indonesia’s automotive vocational education